Tradição, linguagem e orientação: a escrita da história de Manoel Bomfim (1923-1931) - Carolina de Oliveira Silva Othero (2019)
This dissertation has as its object the history of Brazil written by Manoel Bomfim, more specifically his trilogy about the "national formation". The essays Brasil na América (1929), Brasil na História (1930) e Brasil Nação (1931) were analyzed from the perspective of a history of historiography concerned with the centrality of language in the construction of the past. Our objective was to investigate the conceptual apparatus used by the author to represent the national past and the discursive strategies mobilized in the elaboration of a plot to Brazilian history. We chose as our main methodological strategy the analysis of two concepts that played a central role in the historical representation throughout the essays: tradition and formation. Analyzing the use of these terms was a starting point to understand how a past reality was constructed in the narrative. Two broader concerns are present in this dissertation. The first one is to investigate how the history of Brazil written by Manoel Bomfim sought to answer dilemmas that mobilized many intellectuals throughout the First Republic. Among these dilemmas were: the possibility of building a modern nation, the searching of a Brazilian identity in "national language” and the sense of crisis in the Brazilian Republic. The second concern is to understand how Manoel Bomfim wrote a history of Brazil using conceptual categories, analytical procedures and epistemological conceptions present in different disciplinary fields, all of them in formation at that time. In order to comprehend this writing of history that dialogued with different knowledge and theories, especially those from sociology and psychology, we analyze the trilogy together with another work from Bomfim, published in 1923: the book Pensar e dizer: estudo do símbolo no pensamento e na linguagem.